Variação espaço-temporal da assembleia de peixes nas planícies de maré não vegetadas do estuário do rio Marapanim, litoral norte do Brasil - FEILER, Flaviana Livia (2019)
Estuaries are among the most productive systems of the earth serving especially as spawning and nursery sites, migration routes, and areas supporting large populations of coastal fish species. The present study investigated the spatial and temporal patterns of fish assemblage of intertidal mud flats in the Marapanim estuary, North Brazil. The fish of three sites located along of 14.5 km were sampled monthly from August 2006 to July 2007 at ebb tides day during the new moon (spring tide). For each sampling event, water surface salinity and temperature were recorded. The fish sampling was conducted by a beach seine net. The fish fauna was fixed in formol 4% and conserved in alcohol 70%. Catches were transported to the laboratory, measured (total length), weighed and identified to the lowest taxonomic level possible. A total of 1686 individuals (4960.72 g) belonging to 38 species of 20 families were caught. Of 38 species captured in this study only two (5%) Colomesus psittacus and Lycengraulis grossidens were observed in all months of collection, whereas 16 (42%) were observed in all areas of the estuary during the study period. The density and biomass showed a seasonal pattern with significant differences between months. No evident spatial patterns were observed on fish fauna composition. Juveniles of most fish species are present year round, indicating that there is no well defined period of juvenile recruitment in the intertidal mud flats.